2020
DOI: 10.1080/21505594.2020.1785815
|View full text |Cite
|
Sign up to set email alerts
|

PE_PGRS proteins ofMycobacterium tuberculosis: A specialized molecular task force at the forefront of host–pathogen interaction

Abstract: To the PE_PGRS protein subfamily belongs a group of surface-exposed mycobacterial antigens that in Mycobacterium tuberculosis ( Mtb ) H37Rv accounts to more than 65 genes, 51 of which are thought to express a functional protein. PE_PGRS proteins share a conserved structural architecture with three main domains: the N-terminal PE domain; the PGRS domain, that can vary in sequence and size and is characterized by the presence of multiple GGA-GGX amino acid repeats; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 101 publications
4
53
0
Order By: Relevance
“…PE and PPE protein families take their names from conserved motifs in their N-terminal regions [ 57 ]: specifically in residues 7–8 (proline–glutamic acid) for PE and 7–9 (proline–proline–glutamic acid) for PPE [ 56 ]. From almost 100 known representatives of the PE protein family [ 58 ], we can distinguish three subfamilies, including (i) the PE-only subfamily (< 100 aa in length), which is typically associated with a PPE protein to form a heterodimer; (ii) the PE_unique subfamily, which presents unique amino acid sequences of various length at the protein C-terminal side [ 59 ], such as the LipY triacylglycerol lipase, embedding an α/β hydrolase responsible for the hydrolysis of intracellular and extracellular triacylglycerol (TAG); (iii) the PE_PGRS subfamily, which contains numerous glycine-rich sequences (GGA-GGX repeats) [ 60 , 61 ]. Over 60% of the known PE proteins belong to the PE_PGRS subfamily [ 58 ].…”
Section: The Pe_pgrs Family Of Surface Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…PE and PPE protein families take their names from conserved motifs in their N-terminal regions [ 57 ]: specifically in residues 7–8 (proline–glutamic acid) for PE and 7–9 (proline–proline–glutamic acid) for PPE [ 56 ]. From almost 100 known representatives of the PE protein family [ 58 ], we can distinguish three subfamilies, including (i) the PE-only subfamily (< 100 aa in length), which is typically associated with a PPE protein to form a heterodimer; (ii) the PE_unique subfamily, which presents unique amino acid sequences of various length at the protein C-terminal side [ 59 ], such as the LipY triacylglycerol lipase, embedding an α/β hydrolase responsible for the hydrolysis of intracellular and extracellular triacylglycerol (TAG); (iii) the PE_PGRS subfamily, which contains numerous glycine-rich sequences (GGA-GGX repeats) [ 60 , 61 ]. Over 60% of the known PE proteins belong to the PE_PGRS subfamily [ 58 ].…”
Section: The Pe_pgrs Family Of Surface Proteinsmentioning
confidence: 99%
“…This feature, also observed for the PE domains of PE/PPE complexes, suggests that either the PE domain of PE_PGRS33 forms homodimers or it is prone to interact with another protein to form a heterodimer. It is hitherto not clear whether PE_PGRS proteins require a protein partner [ 59 , 86 ], as in the case of PE/PPE proteins. Indeed, pe_pgrs genes are expressed as single operons.…”
Section: Structural Features Of Pe_pgrs33 the Pe_pgrs Prototypementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an increasing number of reports have shown that the mycobacterial PE_PGRS proteins play critical roles in bacterial pathogenesis and immune evasion (De Maio, Berisio, Manganelli, & Delogu, 2020; Meena, 2019). The PE_PGRS protein family, characterized by a special N‐terminal PE (Pro (P)‐Glu (E) motif) domain and a C‐terminal PGRS (Polymorphic GC‐rich Repetitive Sequences) domain, is restricted mainly to pathogenic mycobacteria, for example, M. tb , Mycobacterium bovis , Mycobacterium ulcerans , Mycobacterium marinum and Mycobacterium kansasii (Gey van Pittius et al, 2006; Tian & Jian‐Ping, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we also decided to limit the review to proteins that are secreted and released by Mtb which excludes many PE/PPE family proteins because they remain associated with the Mtb cell wall (e.g., . We point the reader to a current and exhaustive review on PE/PPE Mtb proteins (De Maio et al, 2020). In the absence of experimental data, we used SignalP 5.0 (Almagro Armenteros et al, 2019) to predict the presence of a signal peptide which indicates secretion via the SecA1/2 or Tat secretion systems.…”
Section: Mtb Effector Proteins and Their Targets In The Host Cellmentioning
confidence: 99%